2012
DOI: 10.1371/journal.pgen.1002901
|View full text |Cite
|
Sign up to set email alerts
|

The PARN Deadenylase Targets a Discrete Set of mRNAs for Decay and Regulates Cell Motility in Mouse Myoblasts

Abstract: PARN is one of several deadenylase enzymes present in mammalian cells, and as such the contribution it makes to the regulation of gene expression is unclear. To address this, we performed global mRNA expression and half-life analysis on mouse myoblasts depleted of PARN. PARN knockdown resulted in the stabilization of 40 mRNAs, including that encoding the mRNA decay factor ZFP36L2. Additional experiments demonstrated that PARN knockdown induced an increase in Zfp36l2 poly(A) tail length as well as increased tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
63
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 39 publications
11
63
1
1
Order By: Relevance
“…The ahg2-1 mutation enhances sensitivity to both phytohormones, a phenotype that has been rarely reported 22 . Our present study showed that this phenotype is caused by dysfunction of mitochondria, supporting the idea that mitochondria have roles in stress responses in plants 37,38 . In addition, given the ahg2-1 phenotype of abnormal crosstalk between ABA and SA, it is presumed that mitochondria are involved in the integration of various stress signals in plants.…”
Section: Discussionsupporting
confidence: 89%
“…The ahg2-1 mutation enhances sensitivity to both phytohormones, a phenotype that has been rarely reported 22 . Our present study showed that this phenotype is caused by dysfunction of mitochondria, supporting the idea that mitochondria have roles in stress responses in plants 37,38 . In addition, given the ahg2-1 phenotype of abnormal crosstalk between ABA and SA, it is presumed that mitochondria are involved in the integration of various stress signals in plants.…”
Section: Discussionsupporting
confidence: 89%
“…PARN, an mRNA decay enzyme, has been studied extensively in vitro at the biochemical levels but very little is known of its biological targets and its role in different cellular conditions. Recently, it has been shown that PARN regulates the expression of genes involved in mRNA metabolism, transcription, and cell motility in mouse myoblasts (6). Our studies indicate that the CstF/PARN complex can decrease the mRNA levels of housekeeping genes under DNA-damaging conditions and of genes involved in cell growth and differentiation under nonstress conditions (5).…”
supporting
confidence: 53%
“…Elsewhere, PARN knockdown in HeLa cells showed that genes involved in the p53 signalling pathway were most significantly affected (24). However, in mouse myoblasts, Lee et al (38) reported no changes in the p53 signalling pathway upon PARN knockdown but did observe reduced abundance of telomere maintenance genes, including Terf1, Terf2, and Rtel1. These observations from independent studies, including our own, suggest that PARN deficiency has an effect on p53 and telomere biology, but in a cell-specific manner.…”
Section: Discussionmentioning
confidence: 99%